Analysis of the Screening Process for TB Case Detection in Gleno Health Centre, Letefoho and Railako in 2022 - Ximenes, Leonardo; Martins, Nelson (MultiTech Publisher, 2024)
Tuberculosis (TB) is a leading cause of death worldwide, killing about 1.5 million people annually. However, over 3 million TB cases are lost annually, not diagnosed or diagnosed but not informed. Pulmonary tuberculosis attacks the parenchyma of the lungs. This research aimed to analyze the TB case detection process at Gleno Health Centre and Letefoho Health Centre using the Analytic Observational method with a Transversal Approach (Cros-sectional). The population involved was all health personnel working at the Gleno Health Centre. The findings showed a significant association between the screening process for detecting tuberculosis cases in the community at Gleno Community Health Centre, Letefoho Community Health Centre, and the screening process for detecting tuberculosis cases in the laboratory at these health centers. There was also a significant association between the screening process for detecting tuberculosis cases in the community at Letefoho Community Health Centre and the screening process for detecting tuberculosis cases in the laboratory at Letefoho Community Health Centre. The research found significant effectiveness in detecting TB cases before and after screening.